2021
DOI: 10.47467/alkharaj.v4i1.348
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Program Zakat Produktif antara BAZNAS dan LAZISMU Kota Surakarta

Abstract: This study aims to compare the productive zakat program between Baznas Surakarta City and Lazismu Surakarta City and to study the disadvantages and advantages of these zakat institutions in distributing productive zakat. This research uses descriptive qualitative research methods. Sources of data obtained by in-depth interviews with representatives of zakat and mustahik institutions. Sources of data obtained through literature related to productive zakat. The results of this study indicate that Baznas and Lazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In addition, BAZNAS Karanganyar Regency is a religious organization/institution formed by the government that aims to improve the quality of the community classified as poor and other zakat Mustahiq in the fields of education, da'wah, health, economy and social humanity by maximizing the potential of Muslims, especially through zakat funds, infaq, sadaqah and waqf [42] The use of Zakat Iinfaq Sedekah (ZIS) funds from BAZNAS Karanganyar Regency as stated on its official website is carried out by implementing the following programs: (1) Karanganyar Peduli; (2) Karanganyar Sehat; (3) Smart Karanganyar; (4) Karanganyar Makmur; (5) Karanganyar Taqwa (BAZNAS Karanganyar Program, 2020). In point 4, there is a productive zakat program with an assisted village model called the Barokah Village Program which is located in the Language Tourism Village (KWB) [50], [51].…”
Section: National Amil Zakat Agency (Baznas) Karanganyar Regencymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, BAZNAS Karanganyar Regency is a religious organization/institution formed by the government that aims to improve the quality of the community classified as poor and other zakat Mustahiq in the fields of education, da'wah, health, economy and social humanity by maximizing the potential of Muslims, especially through zakat funds, infaq, sadaqah and waqf [42] The use of Zakat Iinfaq Sedekah (ZIS) funds from BAZNAS Karanganyar Regency as stated on its official website is carried out by implementing the following programs: (1) Karanganyar Peduli; (2) Karanganyar Sehat; (3) Smart Karanganyar; (4) Karanganyar Makmur; (5) Karanganyar Taqwa (BAZNAS Karanganyar Program, 2020). In point 4, there is a productive zakat program with an assisted village model called the Barokah Village Program which is located in the Language Tourism Village (KWB) [50], [51].…”
Section: National Amil Zakat Agency (Baznas) Karanganyar Regencymentioning
confidence: 99%
“…A study conducted by Yoghi regarding the application for zakat funds at a BAZNAS found as many as 4 respondents who expressed difficulties in the process of applying for loan funds or 10% of the total respondents [57]. Another study, also states that the mechanism for applying for business capital or means of production, namely in the preparation of proposals made by Mustahiq himself, although if he later finds difficulties in making, it will be assisted by the zakat institution [50].…”
Section: Mrs Harvini (Ornamental Plant Buying and Selling Business) I...mentioning
confidence: 99%
“…in East Java and Surakarta and has succeeded in helping the community's economy (Hakim et al, 2021). Qarḍ al-ḥasan as part of interest-free philanthropy aims to alleviate the problem of poverty on a humanitarian basis (Musari, 2019).…”
Section: The Dynamics Of the Lazismu Movement In Indonesiamentioning
confidence: 99%
“…Zakat is one of the third pillars of Islam, obliged to every muslim which has an impact on the economy (Hakim et al, 2021). These obligations must be paid so that the assets obtained are always circulated in productive ways.…”
Section: Introductionmentioning
confidence: 99%